Protective effect of oregano and sage essentials oils against the effect of extracellular H2O2 and SNP in Tetrahymena thermophila and Tetrahymena pyriformis - Papa Daouda Mar; Bouchra El Khalfi; Abdelaziz Soukri (Journal of King Saud University: Science, 2020)
Oxidative stress results from an imbalance between the intracellular antioxidants and the radicals ROS or RNS, in favor of the latter. Oxidative stress is associated with several human diseases and causes significant cellular damage to the structure, nucleic acids (DNA, RNA), proteins and lipids. These consequences can compromise the health and viability of the living cell by causing cell death by necrosis or apoptosis.A variety of antioxidant supplements have been developed in recent years to enrich the endogenous defense systems of living organisms. However, the prevention of chronic diseases through the use of antioxidant supplements remains controversial until now. However, natural products with regard to essential oils are very much in demand in biology research because of their antimicrobial and antioxidant properties.We investigated the protective effect of oil of oregano and sage against the oxidative stress induced by hydrogen peroxide (H2O2) and sodium nitroprusside (SNP) in two cellular models Tetrahymena thermophila and Tetrahymena pyriformis. The results of our study showed that oxidative stress inhibits growth, mobility and changes in cell shape of both species. The application of essential oils has shown that both oils protect cells treated with H2O2 and SNP. However, the intracellular mechanism of SNP inhibition is longer than that of H2O2. Therefore, the use of these essential oils could be important to the prevention of chronic diseases related to oxidative stress in higher organisms. Keywords: Oxidative stress, Hydrogen peroxyde, Sodium nitroprusside, Tetrahymena, Essentials oils